Factors Associated with Anemia Occurrence in Young Women in Kambaniru District Puskesmas area East Sumba Regency - Sukartiningsih, Maria Christina Endang; Amaliah, Mega (Poltekkes Kemenkes Kupang, 2018)
Background: Girls are at higher risk than young man, girls are vulnerable to anemia. Iron deficiency anemia is the largest cause of anemia in Indonesia and other developing countries, more than 50 %of anemia is iron deficiency anemia (Briawan, 2014). The purpose of this study analyzing the relationship of predisposing, enabling and strengthening factors of adolescent girls with the incidence of anemia in the working area of Puskesmas Kambaniru. Methods: The research method is Observational Analytical research with Cross Sectional study design research approach. This research was conducted in September – October 2017 on adolescent girls in working area of Puskesmas Kambaniru. The sampling technique used is Simple Random Sampling, a large sample of 87 respondents from the total population of 671 young woman. The Insrument used in this study is a questionnaire. Results: The result of the research will be analyzed by univariate and bivariate analysis test using logistic regression. The result of this research can be concluded that stasistically the predisposing factors of the related incidence of female anamia are knowledge (0,000), attitude (0,002) and diet (0,000) while the boosting factor is health personnel (0,000). Conclusion: The result of this study can be concluded that stasistically that predisposition factors from the incidence of anemia in adolescent girls related are variable knowledge, attitude, diet, while the strengthening factot is healt worker.